Super simple RealTime big data backend : Crate Data - Batlogg, Jodok (O'Reilly Media, 2014)
"Crate Data is a shared-nothing, fully searchable, document-oriented cluster data store. Today, developers need to "glue" several technologies together to store documents, blobs and support searches and queries in near real time over big data. This isn't always simple or scalable and requires a lot of manual tuning, sharding etc. Crate Data is an open source project that attempts to provide a super simple developers' nirvana-a real time SQL data store for big data-using elasticsearch, Lucene, Netty and Presto. In this webcast we will demonstrate, step-by-step example how a web service can be deployed with the full service stack (data and application) on a single node and then add nodes as needed just by starting them. Crate is self-configuring and self-healing and can be deployed on one device, many devices or the cloud."--Resource description page.